Photochemical synthesis of nanocomposite thin films containing silver and gold nanoparticles with 2-thioxanthone thioacetic acid-dioxide and their role in photocatalytic degradation of methylene blue - Kazancioglu, Elif Ozcelik; Aydin, Meral; Arsu, Nergis (ELSEVIER, 2021)
In this study, to see the effect of photoreducing agent on the size, shape and distribution of metallic, Ag and Au nanoparticles were synthesized in the presence of a new one component type II photoinitiator namely 2-thioxanthone thioacetic acid-dioxide. In-situ formation of metallic nanoparticles both in solution and polymer matrix was achieved in a very short timescale. The effect of the photoinitiator concentration on the nanoparticle size, shape and distribution was investigated and the characterization of the obtained nanoparticles was performed by UV-Vis spectrophotometry, DLS and SEM techniques. Compared to other thioxanthone initiators, the results indicate that in the in-situ photoreduction process 2-thioxanthone thioacetic acid-dioxide performs better and process completes in a very short time and the size of nanoparticles are relatively smaller. Additionally, photocatalytic degradation of methylene blue was achieved with the prepared metallic nanocomposite films and Au nanoparticles containing nanocomposite film helped the photodegradation of methylene blue solution better than Ag nanoparticles, nanocomposite films containing Ag nanoparticles and Au nanoparticles degraded the 10 ppm methylene blue solution 58.3% and 63.4%, respectively during 1 minute of irradiation time.
Keywords: silver nanoparticles; gold nanoparticles; photopolymerization; thioxanthone-dioxide; photocatalytic degradation; PHOTOINDUCED ELECTRON-TRANSFER; IN-SITU SYNTHESIS; POLYMER MATRIX; PHOTOINITIATOR; Chemistry; Materials Science; Physics